Loss of vision in a bleeding peptic ulcer patient following resuscitation - an unusual cause of non-arteritic anterior ischaemic optic neuropathy (Journal of Bangladesh College of Physicians and Surgeons, 2010)
A 55-year old male, known to have peptic ulcer disease for 4 years, started haematamesis and melaena in a rural area of Bangladesh and was admitted into hospital with circulatory collapse. He was resuscitated with 8 units of whole blood transfusion and became stable. But he developed sudden loss of vision and fundoscopy revealed bilateral papilloedema but CT scan appeared normal. Clinical and ophthalmological evaluation was consistent with non-arteritic anterior ischaemic optic neuropathy. Key words: optic neuropathy; peptic ulcer   DOI: 10.3329/jbcps.v26i1.4234 J Bangladesh Coll Phys Surg 2008; 26: 50-54